Infrastructure concessions in Peru: recommendations in the light of auction theory - Bonifaz F., Jose Luis (1999)
The private investment in the concessions program of infrastructure in Peru will be US$M 13,700 for the period 1999-2001. Thus, it’s very important for this process to be accomplished in the best way. This means that the concession's winner will be the more efficient firm. The purpose of this work is to present, from auction theory, its most important applications over the concessions of infrastructure. Two of the methods used to define the auction variable are analized: Minimum Toll (fixed term) and Least Value Present of Income (variable term). Finally, we give some basic recommendations to achieve that the auction mechanism reaches the proposed objectives.